A narrative review: clinical trials in therapeutic interventions for dystonia (2020 - 2025) - Ann Ly; Ann Ly; Afreen Mushtaheed; Afreen Mushtaheed; Monica E. Soliman; Monica E. Soliman; Barbara Karp; Barbara Karp; Hyun Joo Cho; Hyun Joo Cho (Dystonia)
Dystonia is a disabling movement disorder affecting millions of people. Approach to managing this disorder in clinical practice include oral and intrathecal medication therapy, botulinum toxin injections, deep brain stimulation, rehabilitative regimens, or a combination of these. This paper is a comprehensive narrative journal review of the most recent clinical trials that were published or completed in the past 5 years or are ongoing (January 2020 to January 2025). The focus of this review it to discuss various treatment modalities and their respective outcome measure. The clinical trials described in this paper and their recent advancements are laying the foundation for future treatment trials.